Clinical utility of skin karyotype - Luiza E. Dorfman; Agnes F. R. P. Silva; Giorgio A. Paskulin; Rafael F. M. Rosa; Paulo R. G. Zen (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACTWe report the case of a patient with Patau syndrome, diagnosed by skin karyotype, emphasizing the applications and importance of this test. The pregnancy morphology ultrasound showed face defects and of central nervous system and heart chambers asymmetry. In the postnatal evaluation it was identified microcephaly, single central nostril, and other malformations. We performed skin karyotype that resulted in full trisomy 13. Our report highlights the possibility of performing karyotype examination in cases when it is no longer possible to obtain a blood sample, thus providing the correct diagnosis and genetic counseling for the family.